PELATIHAN AKUPRESUR UNTUK KADER KESEHATAN SEBAGAI SALAH SATU BENTUK PEMBERDAYAAN MASYARAKAT DALAM MENGENDALIKAN PENYAKIT DEGENERATIF DI DUSUN COKROKONTENG SIDOARUM GODEAN SLEMAN YOGYAKARTA - Dwi Antara Nugraha (Universitas Aufa Royhan Di Kota Padangsidipuan, 2026)
Hypertension is a disease that is suffered by many Indonesian people and is always in the top 10 non-communicable diseases as well as being part of the 10 non-communicable diseases that cause death. In Sleman district, the prevalence of hypertension in 2021 and in the 2022 update still ranks first. The prevalence of degenerative disease sufferers in Sleman district is the basis for thinking, how important it is to control hypertension which is a degenerative disease, so as to provide optimal conditions for the quality of life for the community. Acupressure training at acupuncture points GV 20, GB 20, EX-HN 3, EX-HN 5, GB 21, LI 4 and PC 6 with massage techniques and turning left 30 times each acupoint with a rhythm in harmony with breathing for health cadres in posyandu may be able to help the effectiveness of conventional treatment that has been carried out. The training was given to 12 health cadres. The results of the training on the training score showed a significant difference in the average knowledge score between the score before (M=56.67, SD 9.85) and the score after (M=80.83, SD 7.93), t(11), 6.384, and p=0.000. Suggestions that can be given are the need for socialization and training to health cadres about acupressure therapy for hypertension. Keywords: Hypertension; Acupressure